2012
DOI: 10.1007/s11033-012-1908-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of glutathione S-transferase P1 gene polymorphism with the susceptibility of lung cancer

Abstract: The conclusions of the published reports on the relationship between glutathione S-transferase P1 (GSTP1) gene polymorphism and the risk of lung cancer are still debated. GSTP1 is one of the important mutant sites reported at present. This meta-analysis was performed to evaluate the association between GSTP1 and the risk of lung cancer. The association investigations were identified from PubMed and Cochrane Library, and eligible studies were included and synthesized using meta-analysis method. Forty-four repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The results indicated that GSTP1 polymorphism was not significantly associated with prostate cancer 30, esophageal cancer 32, head and neck cancer 33, lung cancer 34, ovarian cancer 36 and thyroid cancer 37; this polymorphism might contribute to the development of gastric cancer 31 or breast cancer 35 in East Asians, but not in other ethnic populations. However, besides our study, these meta-analyses did not consider the effect of gene-gene and gene-environment interactions in the development of cancer.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The results indicated that GSTP1 polymorphism was not significantly associated with prostate cancer 30, esophageal cancer 32, head and neck cancer 33, lung cancer 34, ovarian cancer 36 and thyroid cancer 37; this polymorphism might contribute to the development of gastric cancer 31 or breast cancer 35 in East Asians, but not in other ethnic populations. However, besides our study, these meta-analyses did not consider the effect of gene-gene and gene-environment interactions in the development of cancer.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, many meta-analyses have been performed to investigate the association between GSTP1 Ile105Val polymorphism and many types of cancer risk (e.g., prostate cancer 30, gastric cancer 31, esophageal cancer 32, head and neck cancer 33, lung cancer 34, breast cancer 35, ovarian cancer 36 and thyroid cancer 37). The results indicated that GSTP1 polymorphism was not significantly associated with prostate cancer 30, esophageal cancer 32, head and neck cancer 33, lung cancer 34, ovarian cancer 36 and thyroid cancer 37; this polymorphism might contribute to the development of gastric cancer 31 or breast cancer 35 in East Asians, but not in other ethnic populations.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al found that smoking could modify the effects of X-ray cross-complementing group 1 and excision repair cross-complementing group 2 polymorphisms on the risk for lung cancer, indicating a gene–environmental interaction in the lung carcinogenesis [36]. It has been well-established that there is a range of genetic susceptibility to lung cancer risk, such as microsomal epoxide hydrolase 1, matrix metalloproteinase-1, and glutathione S -transferase P1 [3739]. In addition, the polymorphism of p53 codon 72 Arg/Pro also has been demonstrated to modify the risk for lung cancer among Asians in many previous case–control studies [21–34].…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al [ 18 ] on the combined effects of GSTM1 present/null and GSTT1 present/null polymorphisms with LC risk will be considered as “positive” result in the overall population, Ye et al [ 15 ] on the GSTM1 null genotype with LC risk in all races, Liu et al [ 41 ] on the GSTM1 null genotype with LC risk in Chinese populations, and Xu et al [ 33 ] on the GSTP1 IIe105Val polymorphism with LC risk will be considered as “positive” results because their studies represent the most credible findings. Li et al, [ 28 ] Sengupta et al, [ 50 ] Yang et al, [ 19 ] Yang et al, [ 34 ] Wang et al, [ 40 ] and Feng et al [ 21 ] will be classified as less-credible results (higher heterogeneity, lower statistical power, FPRP > 0.2 and BFDP > 0.8).…”
Section: Resultsmentioning
confidence: 99%